Analysis Of The Effect Of Service Quality And Price On Customer Satisfaction At The Astaka Motor Workshop In Sendangmulyo, Semarang - Aldo Marvin Aritonang; Siti Kholifah; Fujiama Diapoldo Silalahi (LPPM Universitas Sains dan Teknologi Komputer, 2026)
This study examines whether service quality and price influence customer satisfaction at Astaka Motor Workshop in Sendangmulyo, Semarang. The topic is important because workshop customers usually judge a service not only from the technical repair result, but also from the speed of handling, the clarity of communication, the fairness of the cost, and the overall feeling of trust. The study uses a quantitative associative-causal design with 70 respondents selected through purposive sampling. A structured questionnaire was prepared using a five-point Likert scale and analyzed through descriptive statistics, validity and reliability testing, classical assumption testing, multiple regression, a t-test, an F-test, and the coefficient of determination. The results indicate that both service quality and price have a positive and significant effect on customer satisfaction. Service quality shows the stronger influence, which means that customers pay close attention to punctuality, communication, staff behavior, and the consistency of repair results. Price is also significant because customers want charges that feel fair, transparent, and aligned with the benefits received. The combined model explains a large portion of customer satisfaction and suggests that workshop management should improve service consistency, shorten response time, and provide more transparent pricing information. The study contributes a practical service-marketing perspective for motorcycle workshops in competitive urban markets.